XXth century 2 plays - Jacob, Malou Leviste (Diliman, Quezon City University of the Philippines Press, 2009)
These two plays dissect the violence inflicted on Filipinos by Filipinos.
Country in search of a hero -- A significant life -- Bayang pinagtaksilan ng panahonp (Country in search of a hero) -- Huling salubong (a significant life)
English and Filipino.
Keywords: Philippine drama (English) -- 20th century; Filipino drama -- 20th century; Political satire, Tagalog; Political satire, Tagalog -- Translations into English; Satirical plays, Tagalog